ST-Vector Orientation and Location of Myocardial Perfusion Defects during Exercise - Simoons, M.L.; Withagen, A.; Vinke, R.; Kooy, P.; Bakker, W. (Nuklearmedizin - NuclearMedicine, 1978)
In 34 patients with chest pain the spatial orientation of the ST-vectors in the exercise electrocardiogramm 30 and 80 msec after the end of QRS were compared with the location of exercise induced local defects of myocardial uptake of 201T1. The following results were obtained:1. The sensitivity and specifity of myocardial perfusion imaging after exercise were the same as those of exercise electrocardiograms;2. No relation could be observed between the location of reduced 201T1 uptake during exercise and the spatial orientation of the ST-vectors.